(untitled) - Sharpe, Pamela J (Hauppauge, NY, 1996)
The book includes eight full-length model tests with questions answered and explaned; a detail recommended study plan; An explanation of the TOEFL with time tables for both long and short forms; written transcript for the listening comprehension sections of tests
Keywords: English language,English language,Test of english as a foreign language; Examinations,Study guides,Textbooks for foreign speakers,Study guides